2021
DOI: 10.1007/s11606-021-06792-8
|View full text |Cite
|
Sign up to set email alerts
|

Do Formulation and Dose of Long-Term Opioid Therapy Contribute to Risk of Adverse Events among Older Adults?

Abstract: BACKGROUND: Chronic non-cancer pain (CNCP) is highly prevalent in older adults and long-term opioid therapy (LTOT) has been used to manage chronic pain. However, the safety of LTOT among older adults with CNCP is not well-established and there is a need to identify therapyrelated risk factors of opioid-related adverse events among older adults. OBJECTIVE: To evaluate the relationship between opioid dose and formulation and the risk of opioid-related adverse events among Medicare-eligible older adults on LTOT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…43 Likewise, the literature is consistent on elevated risks of opioidrelated adverse outcomes when prescribing long-acting opioids, which accounted for 40% of the high-dose other opioid categories in our study. 43,52,53 Our study reported higher risks of opioid-related adverse outcomes for the combination of opioids with and without tramadol, although the estimates had higher magnitudes for nontramadol combination. These findings suggest that more caution is needed when coprescribing more than 1 opioid, and strategies such as opioid rotation, which is shown to help with pain control in cancer patients, 54 may be evaluated for chronic noncancer pain.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…43 Likewise, the literature is consistent on elevated risks of opioidrelated adverse outcomes when prescribing long-acting opioids, which accounted for 40% of the high-dose other opioid categories in our study. 43,52,53 Our study reported higher risks of opioid-related adverse outcomes for the combination of opioids with and without tramadol, although the estimates had higher magnitudes for nontramadol combination. These findings suggest that more caution is needed when coprescribing more than 1 opioid, and strategies such as opioid rotation, which is shown to help with pain control in cancer patients, 54 may be evaluated for chronic noncancer pain.…”
Section: Discussionmentioning
confidence: 54%
“…In a study conducted using Medicare data on individuals with long-term opioid therapy, combination opioid therapy had a 5-fold increase in the odds of opioid overdose compared with short-acting opioids. 52 In comparison to no opioid therapy, a combination of short-acting and long-acting was associated with a 384% increase in the hazard of overdose, whereas shortacting only had a 69% higher hazard of overdose. 43 Likewise, the literature is consistent on elevated risks of opioidrelated adverse outcomes when prescribing long-acting opioids, which accounted for 40% of the high-dose other opioid categories in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Comorbid factors such as history of opioid-induced respiratory depression, renal insufficiency, or mental illness predict increased risk of death with opioid use, as does low income (Salkar et al, 2021). Opioid dose greater than 20 milliequivalents of morphine sulfate, or a long-acting opioid, or a combination short/long-acting opioid all predict increased risk of death in older adults (Salkar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid factors such as history of opioid-induced respiratory depression, renal insufficiency, or mental illness predict increased risk of death with opioid use, as does low income (Salkar et al, 2021). Opioid dose greater than 20 milliequivalents of morphine sulfate, or a long-acting opioid, or a combination short/long-acting opioid all predict increased risk of death in older adults (Salkar et al, 2021). Medicare part D beneficiaries with a history of chronic pain, fibromyalgia, and/or fatigue who filled an opioid prescription had 5.65 times greater odds of filling a high-dose (greater than 120 milliequivalents of morphine sulfate) opioid prescription (Maciejewski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%